2020
DOI: 10.5336/jcog.2020-75635
|View full text |Cite
|
Sign up to set email alerts
|

Superb Microvascular Imaging (SMI) - Doppler Technique in the Evaluation of the Endometrial Polyp and Submucosal Myoma in Postmenopausal Overweight Women

Abstract: Ultrasonography (USG) is an important diagnostic method in the practice of gynaecology. The evaluation of endometrial morphology with Doppler sonography in addition to the two-dimensional USG is important for the diagnosis of endometrial lesions. 1 While the conventional colour Doppler is insufficient to identify vessels smaller than 1 mm and flows lower than 3-5 cm/sec, power Doppler is useful in low flow imaging. 2 Superb Micro Vascular Imaging (SMI) is a new Doppler technique. It displays low blood flow in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…21 Furthermore, conventional Doppler USG may be insufficient due to weak tissue penetration of Doppler echos. 6 Guerriero et al reported that CDI's ovarian vascularity detection rate was 65(21%) and with PDI, this rate increased. 24 Due to artifacts, such as colour confusion and noise, CDI cannot display all Doppler spectrums and is mostly employed in heart and vascular tissues.…”
Section: A) B)mentioning
confidence: 99%
See 4 more Smart Citations
“…21 Furthermore, conventional Doppler USG may be insufficient due to weak tissue penetration of Doppler echos. 6 Guerriero et al reported that CDI's ovarian vascularity detection rate was 65(21%) and with PDI, this rate increased. 24 Due to artifacts, such as colour confusion and noise, CDI cannot display all Doppler spectrums and is mostly employed in heart and vascular tissues.…”
Section: A) B)mentioning
confidence: 99%
“…Some studies have mentioned the SMI Doppler technique's high diagnostic value. 6 A few studies used TAUSG-SMI Doppler imaging in gynaecology cases. 6,9,26 The findings of the current study negated the null hypothesis.…”
Section: A) B)mentioning
confidence: 99%
See 3 more Smart Citations